Controls of eustasy and diagenesis on the 238U/235U of carbonates and evolution of the seawater (234U/238U) during the last 1.4 Myr. (1st December 2018) - Tissot, François L.H.; Chen, Cindy; Go, Benjamin M.; Naziemiec, Magdalena; Healy, Garrett; Bekker, Andrey; Swart, Peter K.; Dauphas, Nicolas
Abstract: Using a leaching protocol designed for the study of U isotopes in recent carbonates, we measured the U isotope composition, both 238 U/ 235 U and 234 U/ 238 U, of modern and ancient corals (n = 6), a limestone and a dolostone, as well as 43 shallow-water carbonate sediments from the ODP Leg 166 Site 1009 drill core, on the slope of the Bahamas platform. Although bulk corals record the seawater δ 238 U value within ±0.02‰, differences of up to 0.30‰ in the δ 238 U of individual leachates suggest a control of the coral structure and a more positive 238 U/ 235 U ratio in the centers of calcification. The drill core δ 238 U data shows that the 238 U/ 235 U ratio of shallow-water carbonates is controlled mainly by (1) variations in sea-level through the mixing of different amounts of platform-derived sediments (with δ 238 U ∼0.50–0.60‰ heavier than seawater) and pelagic sediments (with seawater-like δ 238 U values), (2) authigenic U enrichment via pore-water circulation and U reduction both on the platform and down to ∼5 m below the surface (mbsf) after deposition of the sediment, and, to a lesser extent, by (3) early diagenetic processes ( i.e., carbonate dissolution and/or recrystallization) during sediment burial. The global effect of these processes leaves the δ 238 U values of shallow-water carbonates offset relative to that of seawater by ΔCarbonates-SW = +0.24 ± 0.06‰ (95% CI, including all samples). This shift can be used in seawater paleoredox reconstructions based on carbonates deposited on shallow-water platform, shelf and slope environments ( i.e., most of the carbonate sedimentary record prior to the Mesozoic) to account for the average effect of carbonate diagenesis. Assuming that the 238 U/ 235 U ratio of carbonate platform sediments directly records the seawater 238 U/ 235 U ratio would underestimate the extent of ocean-seafloor anoxia by at least a factor 10. The rapid fluctuations in δ 238 U values due to sea-level changes (i) is a factor that should be considered before interpreting δ 238 U variations as reflecting changes in oceanic paleoredox conditions and (ii) reinforces the need for statistically meaningful data sets. The δ( 234 U) data suggest that the ( 234 U/ 238 U) ratio of the seawater has remained within ∼20‰ of the modern seawater value during the last 1–1.4 Myr. Furthermore, we find that small-scale (1–15‰) variations in seawater δ( 234 U) mirror sea-level changes during the penultimate glacial-interglacial period (∼140 to ∼200 ka), thus confirming the record of lower δ( 234 U)SW during periods of low sea-level stand and expanding it to at least the last two glacial-interglacial events ( i.e., ∼0.23 Ma). Such fluctuations in δ( 234 U)initial values should be taken into account when screening carbonate sediments U-Th ages on the basis of the initial ( 234 U/ 238 U) ratios of the samples.